From the Editor - DeNisi, Angelo (Academy of Management Journal, 1994)
The article presents comments from the editor reviewing the journal's progress in 1994. The author explains his personal experience as editor of the journal, and acknowledges the contributions of editors Maureen Ambrose and Anne Tsui. The author also explains statistics from 1994, including the number of new submissions and forum papers, and the average review time of 53 days. The author states that the editorial team needs to be quicker when reviewing papers and states that readers will have to reach their own conclusions about the differences in the journal's editing procedures.